Technology flows between sectors and its impact on large-scale firms - Jürgen Antony; Thomas Grebel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In this paper we highlight the importance of technology flows between sec- tors and their impact on the labor productivity of large-scale corporations. Based on theoretical considerations, we explore technological spillovers between the sectors of an economy. Large-scale corporations usually focus on certain sec- tors but make use of a wide range of technological knowledge from other sectors. Thereby, technological knowledge built up in sectors by continuous R&D ac- tivities does not spill over without bounds but is directed by firms' absorptive capacities. We use firms' patent portfolio to empirically calculate the sector af- filiation and therewith the firms' absorptive capacities in order to estimate the impact of technology diffusion on labor productivity. Fortune 500 firms serve as data base.
Keywords: O33; O14; 330; Technology Flows; Spillovers; Firm Productivity; Innovationsdiffusion; Wissenstransfer; Großunternehmen; Interindustrielle Verflechtung; Arbeitsproduktivität; Welt